Triclinic modification of di-n-butylbis(2-hydroxybenzoato-κ 2 O 1,O 1′)tin(IV) - Reisi, R.; Misran, Misni; Lo, Kong Mun; Ng, Seik Weng (International Union of Crystallography, 2008)
The Sn atom in the title compound, [Sn(C4H9)2(C7H5O3)2], is chelated by the carboxylate groups of 2-hydroxybenzoate liagnds, and exists in a six-coordinate skew-trapezoidal bipyramidal coordination geometry [C—Sn—C = 140.1 (3)°].